2012
DOI: 10.26719/2012.18.7.735
|View full text |Cite
|
Sign up to set email alerts
|

735 Association between modifiable lifestyle factors and inflammatory markers in patients with metabolic syndrome

Abstract: There is accumulating evidence suggesting that inflammation is the bridging link between cardiovascular disease and metabolic syndrome. Recent studies have shown a relationship between inflammatory markers and modifiable lifestyle factors including fitness, diet, exercise and smoking. We carried out a cross-sectional study of 195 patients with metabolic syndrome. Data on nutritional intake, physical activity level and smoking habits were collected through a questionnaire. Weight and body composition were deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
10
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 26 publications
4
10
0
1
Order By: Relevance
“…Consistent with our results, associations between dietary factors and inflammatory markers have been reported by several studies [5, 7, 8, 2426]. However, not all studies have shown association with CRP [27, 28], similar to our findings.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Consistent with our results, associations between dietary factors and inflammatory markers have been reported by several studies [5, 7, 8, 2426]. However, not all studies have shown association with CRP [27, 28], similar to our findings.…”
Section: Discussionsupporting
confidence: 93%
“…Our finding of the independent association between smoking and IL-6 and TNF-α is substantially supported by the literature [13, 24, 25]. The lack of the association between smoking and CRP may be due to the sequence of the tobacco cascade operation (smoking increases serum concentration of IL-6 and that leads to raised CRP concentration [26]), or timing of the smoking cessation resulting in a delayed decrease of CRP [25]. …”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…In addition, 3-day 24-hour food recall of subjects, including 2 weekdays and 1 weekend day, were collected at baseline and after 60 days to estimate dietary intake of calcium and zinc [13]. The cut-offs for adequate intake of zinc and calcium was defined as 8-40 mg/dL and 1000-2000 mg/dL, respectively [14].…”
Section: Data Collectionmentioning
confidence: 99%